Fabrication And Characterization Of Ag-Al Die Attach Material For Sic-Based High Temperature Device - Vemal , Raja Manikam (2012)

(untitled)
An Ag-Al nanopaste for high temperature die attach applications on SiC power devices has been developed. The Ag-Al nanopaste was studied by varying the Al weight percent in the Ag matrix as well as the organic additives content. The Ag-Al nanopaste was sintered in open air at 380°C for 30 minutes to burn off the organic additives, causing Ag and Al nanoparticles to undergo solid-state fusion. The sintered Ag-Al die attach material’s physical, thermal, electrical and mechanical attributes were examined. X-ray diffraction studies revealed the formation of Ag2Al and Ag3Al compounds in the post-sintered nanopaste. The sample with 80% Ag and 20% Al weight percent content having a total nanoparticle content of 87.0% demonstrated the best electrical and thermal characteristics. Its melting point was 518 ± 1°C. Based on homologue temperature ratios of 0.67-0.85, the Ag80-Al20 die attach material can be used between 258.59°C to 400.18°C. It’s electrical and thermal conductivities were higher than those of solder alloys and conductive epoxies at 1.01 x 105 (ohm-cm)-1 and 123 W/m-K, respectively. The coefficient of thermal expansion was 7.74 x 10-6/°C, which is close to that of SiC and can help minimize thermal mismatch. The Ag80-Al20 sample also had the lowest porosity percentage at 19% amongst all samples and a density value of 6.42 g/cm3. The organic additives used in the nanopaste affected the creation of a dense die attach material as well as the mechanical attributes of the die attach material, i.e. the modulus of elasticity, hardness and stiffness. SiC die back metallization tests concluded that Ag and Au coatings gave the best joint adhesion strength between 28.9 – 38.1 MPa for high temperature power device applications. In essence lower organic additives content improved the attributes of the die attach nanopaste.